Estrutura económico-produtiva, sistema de emprego e qualificações na Construção: uma breve leitura sobre tendências e mudanças recentes - Pinto, José Madureira; Rodrigues, Vanessa; Coelho, Maria Inês (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This article analyses the process of restructuring of the productive system and employment in the construction sector in Portugal, using the reconstitution of official updated statistical series on the subject. In addition to identifying the main changes in these areas over the past decades, some hypotheses on the business segmentation process and about the relationship between employment and professional integration will be explored.